Astroglial Ca2+-Dependent Hyperexcitability Requires P2Y1 Purinergic Receptors and Pannexin-1 Channel Activation in a Chronic Model of Epilepsy - Wellmann, Mario; Álvarez-Ferradas, Carla; Maturana, Carola J.; Sáez, Juan C.; Bonansco, Christian (Frontiers in Cellular Neuroscience, 2018)
Astrocytes from the hippocampus of chronic epileptic rats exhibit an abnormal pattern of intracellular calcium oscillations, characterized by an augmented frequency of long lasting spontaneous Ca2+ transients, which are sensitive to purinergic receptor antagonists but resistant to tetrodotoxin. The above suggests that alterations in astroglial Ca2+-dependent excitability observed in the epileptic tissue could arise from changes in astrocyte-to-astrocyte signaling, which is mainly mediated by purines in physiological and pathological conditions. In spite of that, how purinergic signaling contributes to astrocyte dysfunction in epilepsy remains unclear. Here, we assessed the possible contribution of P2Y1R as well as pannexin1 and connexin43 hemichannels – both candidates for non-vesicular ATP-release – by performing astroglial Ca2+ imaging and dye uptake experiments in hippocampal slices from control and fully kindled rats. P2Y1R blockade with MRS2179 decreased the mean duration of astroglial Ca2+ oscillations by reducing the frequency of slow Ca2+ transients, and thereby restoring the balance between slow and fast transients in the kindled group. The potential contribution of astroglial pannexin1 and connexin43 hemichannels as pathways for purine release (e.g., ATP) was assessed through dye uptake experiments. Astrocytes from kindled hippocampi exhibit three-fold more EtBr uptake than controls, whereby pannexin1 hemichannels (Panx1 HCs) accounts for almost all dye uptake with only a slight contribution from connexin43 hemichannels (Cx43 HCs). Confirming its functional involvement, Panx1 HCs inhibition decreased the mean duration of astroglial Ca2+ transients and the frequency of slow oscillations in kindled slices, but had no noticeable effects on the control group. As expected, Cx43 HCs blockade did not have any effects over the mean duration of astroglial Ca2+ oscillations. These findings suggests that P2Y1R and Panx1 HCs play a pivotal role in astroglial physiopathology, which would explain the upregulation of glutamatergic neurotransmission in the epileptic brain and thus represents a new potential pharmacological target for the treatment of drug-refractory epilepsy.